2022
DOI: 10.12775/jehs.2022.12.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effects on the EEG of drinking monotherapy with Naftussya water and therapy supplemented with “Myroslava” and “Khrystyna” mineral waters

Abstract: Background. Earlier we showed that the newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa have favorable effects on metabolism and neuroendocrine-immune complex of patients with their dysfunction. This report analyzes the effect of balneotherapy on the parameters of the electroencephalogram of the same contingent of patients. Materials and Methods. The object of clinical-physiological observation were 34 men aged 23-70 years, who underwent rehabilitation treatment of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Thus, the mineral waters "Myroslava" and "Khrystyna" have both similar [12,13] and different effects on the body. It is important that the differences are manifested not only in the severity of changes in the registered parameters, but also in their direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the mineral waters "Myroslava" and "Khrystyna" have both similar [12,13] and different effects on the body. It is important that the differences are manifested not only in the severity of changes in the registered parameters, but also in their direction.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier we found effects on the neuroendocrine-immune complex and metabolism, which are common to the mineral waters "Myroslava" and "Khrystyna", instead different from the effects of Naftussya water [6,12,13]. The purpose of this article is to find the specific effects of these waters.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Adhering to the principle "Ex experimento ad clinic", we continued research in this direction with the participation of patients of the resort. We showed that these mineral waters have favorable effects on metabolic, HRVs, EEGs, endocrine and immune parameters [8,9]. This article presents an integrated assessment of previously identified effects.…”
Section: Inroductionmentioning
confidence: 91%
“…To correct the consequences of distress, it is necessary to use modulators to restore the balance of homeostasis reactions and not cause side reactions. Mineral waters (MW) of different chemical compositions are considered to be such natural nonspecific modulators [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%